Contributions of Mamu-A*01 status and TRIM5 allele expression, but not CCL3L copy number variation, to the control of SIVmac251 replication in Indian-origin rhesus monkeys. - So-Yon Lim; Tiffany Chan; Rebecca S Gelman; James B Whitney; Kara L O'Brien; Dan H Barouch; David B Goldstein; Barton F Haynes; Norman L Letvin (PLoS Genetics)
CCL3 is a ligand for the HIV-1 co-receptor CCR5. There have recently been conflicting reports in the literature concerning whether CCL3-like gene (CCL3L) copy number variation (CNV) is associated with resistance to HIV-1 acquisition and with both viral load and disease progression following infection with HIV-1. An association has also been reported between CCL3L CNV and clinical sequelae of the simian immunodeficiency virus (SIV) infection in vivo in rhesus monkeys. The present study was initiated to explore the possibility of an association of CCL3L CNV with the control of virus replication and AIDS progression in a carefully defined cohort of SIVmac251-infected, Indian-origin rhesus monkeys. Although we demonstrated extensive variation in copy number of CCL3L in this cohort of monkeys, CCL3L CNV was not significantly associated with either peak or set-point plasma SIV RNA levels in these monkeys when MHC class I allele Mamu-A*01 was included in the models or progression to AIDS in these monkeys. With 66 monkeys in the study, there was adequate power for these tests if the correlation of CCL3L and either peak or set-point plasma SIV RNA levels was 0.34 or 0.36, respectively. These findings call into question the premise that CCL3L CNV is important in HIV/SIV pathogenesis.